PENGARUH STATUS SOSIAL EKONOMI ORANG TUA, LITERASI EKONOMI DAN PERCAYA DIRI TERHADAP MINAT WIRAUSAHA SISWA SMP NEGERI DI KECAMATAN TENGGILIS MEJOYO SURABAYA - Thohir, Muhammad; Soesatyo, Yoyok; Harti, Harti (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
This analysis to know the determine the effect of Socioeconomic Status of Parents of the students 'entrepreneurial interest, Effect of Economic Literacy for students' entrepreneurial interest, Effect on Interest Entrepreneurial Confidence Students and the Effect of Socio economic Status of Parents, Economic Literacy and self Confidence toEntrepreneurial Student Interests with partial and collectively - together/simultaneously in SMP at Mejoyo Tenggilis Subdistrict Surabaya. This study is using multiple linear regression analysis with a quantitative approach.The study population of 686 students and a sample of 253 students was taken by random sampling propotional.Based on the results of research and discussion of the results of this study concluded that the results the Socio-Economic Status of Parents, Economic Literacy, and Self Confidence influence the Entrepreneurial Interests with significant